Mayban Finance Berhad The study on the factors attracting customers to ASN loan at Wangsa Maju branch / Mohd Zamri Abdul Manan - Abdul Manan, Mohd Zamri (1999)
This project paper been conducted in order to gain information regarding the topic of ‘ Mayban Finance Berhad : The study on the factors attracting customers to ASN loan at Wangsa Maju branch This project paper included the background and scope of study whereby it is important in order to identifying factors that could attract customers to take ASN loan whereby from the analysis , it could be use by the Mayban Finance Wangsa Maju branch to increase ASN loan in the future. Two hypothesis have been identified to solve this analysis. Both of it had been accepted which is economic and demographic factors. From this hypothesis , Mayban Finance Wangsa Maju branch could manage to give a good services besides conducting promotion more effective and efficiently. Exploratory study has been identified to be the best method to consider in this research study because it is important to understand what is happening before I could develop a model and set up a rigorous design for complete investigation. 40 respective respondents have been choose randomly by using simple random sampling. Each of them must be 18 years and above whereby survey been conducted from each customers that comes to Mayban Finance Wangsa Maju branch.